Determination of sofosbuvir and velpatasvir in solid pharmaceutical dosage form by hplc-pda and its application to in vitro dissolution studies - Tahir, Muhammad Saqlain; Ahmed, Mahmood; Qadir, Muhammad Abdul; Adnan, Ahmad; Syed, Quratulain; Low, Kah Hin; Ikram, Rabia (Colegio de Farmaceuticos de la Provincia de Buenos Aires, 2018)
In the present study, a newly developed method based on high performance liquid chromatography (HPLC) was optimized for the simultaneous determination of sofosbuvir (SOFOS) and velpatasvir (VELPA) in commercial tablet formulations. Isocratic separation of SOFOS and VELPA was performed at 40 ºC with Purospher Star C18 column (5 μm, 4.6 × 250 mm) at a flow rate of 1.0 mL/min whereas the mobile phase consisted of aceto nitrile, phosphate buffer and methanol (60:30:10 v/v, pH 3.0). Both analytes were detected at a wavelength of 262 nm and the injection volume was 5.0 μL. The overall run time per sample was 7.0 min with retention time of 3.251 and 4.512 min for SOFOS and VELPA, respectively. The calibration curve was linear from 10.0-70 μg/mL for SOFOS and 5.0-35.0 μg/mL for VEL-PA with a coefficient of determination equal to 0.9999 while repeatability and reproducibility (expressed as relative standard deviation) were ≤ 1.32 and 1.61 %, respectively. The proposed HPLC method was rapid and simple for the determination of SOFOS and VELPA in commercially available tablet formulations providing recoveries ≥ 99.4 % and also for dissolution studies.